7х+13.48=97.9

57.3-11х=18.14

17.6:х-2.27=1.73

(х-8.59)*6=17.49

(х+2.67):7=0.86

(5х-23.8):2=37.6

х+х+х+х=5.46

1

Ответы и объяснения

  • Участник Знаний
2013-05-14T15:45:07+04:00

7Х + 13.48 = 97.9

7Х = 97.9 - 13.48
7Х = 84.42
Х = 84.42 : 7 
Х = 12.06
Ответ: Х = 12.06

57.3 - 11Х = 18.14
- 11Х = 18.14 - 57.3
- 11Х = - 39.16
Х = - 39.16 : ( - 11)
Х = 3.56
Ответ: 3.56 
 
17.6 : Х - 2.27 = 1.73

17.6 : Х = 1.73 + 2.27
17.6 : Х = 4
Х = 17.6 : 4
Х = 4.4
Ответ: Х = 4.4
 

(Х - 8.59) * 6 = 17.49
6Х - 51.54 = 17.49
6Х = 17.49 + 51.54
6Х = 69.03

Х = 69.03 : 6
Х = 11.505
Ответ: 11.505

(Х + 2.67) : 7 = 0.86
Х + 2.67 = 0.86 * 7 

Х + 2.67 = 6.02
Х = 6.02 - 2.67
Х = 3.35
Ответ: Х = 3.35

(5Х - 23.8) : 2 = 37.6

5Х - 23.8 = 37.6 * 2
5Х - 23.8 = 75.2
5Х = 75.2 + 23.8
5Х = 99
Х = 99 : 5
Х = 19.8
Ответ: Х = 19.8

Х + Х + Х + Х = 5.46

4Х = 5.46
Х = 5.46 : 4
Х = 1.365
Ответ: 1.365